Exposures to war-related traumatic events and post-traumatic stress disorder symptoms among displaced Darfuri female university students: an exploratory study - Badri Alia; Crutzen Rik; Van den Borne H W (BMC, 2012)
Abstract Background With the deaths of hundreds of thousands and the displacement of up to three million Darfuris, the increasingly complex and on-going war in Darfur has warranted the need to investigate war-related severity and current mental health levels amongst its civilian population. The purpose of this study is to explore the association between war-related exposures and assess post-traumatic stress disorder (PTSD) symptoms amongst a sample of Darfuri female university students at Ahfad University for Women (AUW) in Omdurman city. Methods An exploratory cross-sectional study among a representative sample of Darfuri female university students at AUW (N = 123) was conducted in February 2010. Using an adapted version of the Harvard Trauma Questionnaire (HTQ), war-related exposures and post-traumatic stress disorder (PTSD) symptoms were assessed. Means and standard deviations illustrated the experiential severity of war exposure dimensions and PTSD symptom sub-scales, while Pearson correlations tested for the strength of association between dimensions of war exposures and PTSD symptom sub-scales. Results Approximately 42 % of the Darfuri participants reported being displaced and 54 % have experienced war-related traumatic exposures either as victims or as witnesses (M = 28, SD = 14.24, range 0 - 40 events). Also, there was a strong association between the experiential dimension of war-related trauma exposures and the full symptom of PTSD. Moreover, the refugee-specific self-perception of functioning sub-scale within the PTSD measurement scored a mean of 3.2 (SD = .56), well above the 2.0 cut-off. Conclusions This study provides evidence for a relationship between traumatic war-related exposures and symptom rates of PTSD among AUW Darfuri female students. Findings are discussed in terms of AUW counseling service improvement.